Upaya meningkatkan hasil belajar PKn pada materi menjaga keutuhan NKRI melalui metode bermain peran dengan cooperative learning pada siswa kelas V SD N Sawahan Juwiring Klaten - Tri Santosa (Universitas Sebelas Maret, 2020)
Abstract. This research is a classroom action research (PTK) with research subjects as fifth grade students of SD Negeri 2 Sawahan Juwiring Klaten in the academic year 2017/2018. Data collection methods used in this study are test, interview and observation methods. The collected data were analyzed by descriptive analysis. Based on data analysis, it can be concluded that: 1) Through the role playing method with cooperative learning approach, it can improve PKN learning activities to maintain the integrity of the Unitary Republic of Indonesia in fifth grade students of SD Negeri 2 Sawahan Juwiring Klaten in the academic year 2017/2018. This is reflected in the average activity of cycle I reaching 57.35% and increasingto 76.4% in cycle II; 2) Through the role playing method with cooperative learning approach, it can increase PKN learning activities to maintain the integrity of the Unitary Republic of Indonesia in fifth grade students of SD Negeri 2 Sawahan Juwiring Klaten in the academic year 2017/2018. This can be shown by increasing: (1) The average value in the pre-study obtained an average class of 66 with 28.57% mastery learning, (2) in the first cycle obtained an average grade of 76.94 with mastery learning 71 , 4%, (3) and in the second cycle obtained an average grade of 83.69 with 85.7% mastery learning. This shows that the PKn learning outcomes of students reach the completeness target of> 85% with a KKM value of> 70.